MILLIY MUSIQIY MEROSNI O’RGANISHNI UZLUKSIZLIK VA UZVIYLIK TAMOYILI ASOSIDA TASHKIL ETISH: MUAMMO VA YECHIMLAR - Qudratov, I. (SCIENCE and SOCIETY, 2019)
One of the social requirements in the system of continous education today is the upbringing of the youth on the basis of classical heritage of Uzbek music and developing such qualities as spiritual stability, self-realization, aesthetic education and respect for the national traditions.
Keywords: music; lesson; education; folk music; musical heritage; continuity; systematicity